Carrots and sticks: Targeting the opposition in an autocratic regime - Cathrin Mohr (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2023)
Autocratic regimes can use carrots and/or sticks to prevent being overthrown by protests. Carrots, i.e. resource allocation, reduce the probability of protests, but cannot help to end them. Sticks, i.e. repression, reduce the probability that protests overthrow the regime, but also decrease its popularity. Using a difference-in-differences approach, I show that residential construction and military presence increase in protest municipalities after an uprising in 1953 in former East Germany. This cannot be explained by preexisting differences, demand for housing, or external warfare considerations. Carrots were furthermore used to counteract sticks' negative effect on popularity. More construction is associated with more regime support.
Keywords: D72; D74; N44; P26; 330; Political Economy; autocracy; Protests